Elastins-based antimicrobial particles for delivery of bioactive compounds - Machado, Raul (2020)
In the development of drug delivery systems, researchers pursue multifunctionality to target more complex problems, while maintaining biocompatibility and high encapsulation efficiency. Herein, we describe the preparation of noncytotoxic particles with intrinsic antimicrobial properties able to entrap bioactive compounds. The particles are composed of a recombinantly produced elastin-like recombinamer functionalized with an antimicrobial peptide, and are spontaneously formed in mild conditions by exploiting the thermoresponsiveness of the elastin-like portion. This chapter provides advice and methods for the preparation of the self-assembled antimicrobial particles, the evaluation of antimicrobial activity and cytotoxicity, and the basis to set up the methodology for the encapsulation of bioactive compounds.